When Geography Matters: International Diversification and Firm Performance of Spanish Multinationals - Espinosa-Mendez, C (SAGE Publications Inc., 2020)
This paper studies how the nature and shape of the relationship between inter-national diversification (ID) and performance (P) may vary according to a firm’s geographical focus of internationalization. Using a sample of Spanish multinational firms for the 2004—2012 period we find an M-shaped relationship. However, significant differences are found when the different geographical foci of internationalization are considered. Strong support is found when firms adopt a regional focus (an inverted S-curve when the ID measure refers to the number of foreign countries and an M-curve when it refers to the size of the network of foreign sub-sidiaries), a biregional focus (an S-curve) and a semiglobal focus (an inverted S-curve but also an M-curve with foreign subsidiaries). These findings and their pattern suggest the critical impor-tance of the country of origin and the geographical focus of internationalization in explaining the relationship between ID—P. © The Author(s) 2020.
Keywords: International diversification; Firm performance; Geographical focus; M-curve; Spain; Multinational firms